VD_FINDINFO Jug / 2021 / 106 vom 17. September 2020 - VD Tribunal cantonal (2020)
RISQUE DE FUITE, MISE EN LIBERTÉ PROVISOIRE, DEMANDE ADRESSÉE À L'AUTORITÉ, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 233 CPP (CH)